PARADOJAS ENTRE OBJECTIVOS Y RESULTADOS DE POLÍTICAS PÚBLICAS. ANÁLISIS COMPARADO DEL AUTO TRANSPORTE COLECTIVO DE BUENOS AIRES. - Gutiérrez, Andrea (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2006)
Buenos Aires public bus transport is renown abroad for its good level of service without subsidy, on behalf of small private enterprises under public regulation. As in other parts of the world, in the 90´s it was a regulatory revision which objective is to encourage improvements without structural changes. After ten years, the results show paradoxes. On one hand, subsidies are not the cause of the revision but it takes place after it. On the other hand, the regulation introduces small and rather formal changes but a different enterprise and service profile emerges. Finally, there are results in common with other international experiences of different orientation. The paper aims to interpret the paradoxes between objectives and results of public policies, organizing the empirical evidence through a methodological scheme applied to the integrated (public services and free offer services) and comparative (with international experiences) analysis of the case. Finally, it tries a theoretical reflection about the urban bus transport, looking for shared tendencies and identifying continuities and ruptures with previous moments.